THE READINESS OF THE SEMARANG CITY POLICE IN FACING SECURITY CHALLENGES ARISING FROM SOCIAL DYNAMICS AHEAD OF THE 2024 ELECTIONS - Ivan Pradipta Mahadika; Chrysnanda Chrysnanda; Muhamad Erza Aminanto (Transpublika Publisher, 2024)
Indonesia's diverse culture and society, with its many islands, ethnic groups, and languages, present unique challenges for elections. Exploiting social differences in political competition can create tensions and conflicts. Sensitive issues like ethnicity, religion, race, and social groups, along with the spread of false information through social media, increase the risks. Past conflicts in Central Java and Semarang after elections highlight the danger of misunderstandings between groups. The Semarang Police must prepare for the 2024 elections by training personnel, collaborating with relevant organizations, using technology, raising community awareness, managing false information, and planning secure campaign events. The readiness of the Semarang Police is crucial in maintaining stability and preventing conflicts during the upcoming elections. This study aims to elucidate how the Semarang Police Station is prepared to face security challenges arising from social dynamics leading up to the 2024 elections. This research employs a qualitative method, drawing on national security theory, community policing theory, and the concept of readiness as theoretical frameworks. The 2024 elections in Indonesia raise concerns about security due to social dynamics. The Semarang Police Station plays a vital role in preparing for these challenges. This involves monitoring social dynamics, training personnel, collaborating with stakeholders, and enhancing conflict and security management. Despite the challenges of managing a diverse society, Indonesia's values of tolerance, inter-religious harmony, and gotong royong are sources of national strength.